Subcutaneous protein C concentrate in the management of severe protein C deficiency – experience from 12 centres. (February 2014) - Minford, Adrian; Behnisch, Wolfgang; Brons, Paul; David, Michele; Gomez Gomez, Natividad; Hertfelder, Hans‐Joerg; Kruempel, Anne; Kurnik, Karin; Mathias, Mary; Molines Honrubia, Antonio; Monagle, Paul; Morgan, Mary; et al.
Summary Since the first description of subcutaneous protein C concentrate as treatment for severe protein C deficiency in 1996, further cases have been reported but there is no uniform approach to this form of treatment. In order to assess the safety and effectiveness of subcutaneous protein C concentrate and suggest recommendations for future use, patients who had received subcutaneous protein C concentrate were identified from the literature, by contacting the manufacturers and by personal communication. Treatment details were available from 14 cases. Apart from one case where the infusion interval was inadvertently increased, no thrombotic events occurred even when doses were subsequently reduced. Initially, a trough protein C level of >0·25 iu/ml should be aimed for. Subsequently, a smaller dose of subcutaneous protein C concentrate, especially if taken with an oral anticoagulant, may be protective maintenance treatment. The treatment was well tolerated with few side effects. Subcutaneous protein C concentrate on its own or combined with an oral anticoagulant appears to be safe and effective as maintenance treatment of severe protein C deficiency. A major advantage is the avoidance of central venous access devices. The incidence of neurodevelopmental handicap was high with blindness affecting the majority of patients.